Gênero discursivo cinema, o filme musical: análise dialógica de Across the Universe - Serni, Nicole Mioni [UNESP] (2014)
Considering cinema as a fertile genre for the studies of dialogue between genres this research thinks about the musical film Across the Universe (2007), by Julie Taymor, in its architectonic (form, style and content). The cinema genre and the song genre are in constant dialogue in the musical film and specifically in the corpus chosen. The songs within the movie are all composed by the british band The Beatles. The dialogical relations and the genres recognized in this research are analyzed within the perspective of the studies of the Bakhtin Circle Bakhtin, and aim to analyze how the movie Across the Universe incorporates the songs by The Beatles and in which way the musical dialogues with the lyrics of each song and with each situation in which they are sung in the movie. Within the dialogical perspective of the Circle the analysis of the movie makes it possible to recognize the cinema as composed by other genres that are incorporated within its composition, such as in Across the Universe, in which song and dance are part of the composition of the musical film